Tautomerism in cytosine and uracil: a theoretical and experimental X-ray absorption and resonant auger study - Feyer, Vitaliy; Plekan, Oksana; Richter, Robert; Coreno, Marcello; De Simone, Monica; Prince, Kevin C.; Trofimov, Alexander B.; Zaytseva, Irina L.; Schirmer, Jochen (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2010)
The core level photoabsorption spectra of the nucleobases cytosine and uracil in the gas phase have been measured and the results interpreted with theoretical calculations using an ab initio Green’s function approach. A single tautomer of uracil is populated, in agreement with previous work, while three tautomers of cytosine are clearly identified, whose identity and relative populations at the temperature of the experiment were reported previously. The second-order ADC approach to polarization propagator was employed in calculations of X-ray photoabsorption energies and intensities. The theoretical spectra have been constructed as Boltzmann-factor-weighted sums of individual tautomer spectra. These theoretical spectra are in good agreement with the experimental photoabsorption results at the oxygen, nitrogen, and carbon edges. In addition we report resonant Auger spectra of the valence band of cytosine, which support previous assignments of the character of the valence band states.
Gesehen am 24.04.2023